2023
DOI: 10.1101/2023.11.01.565196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal stability of individual brain plasticity patterns in blindness

Lénia Amaral,
Peyton Thomas,
Amir Amedi
et al.

Abstract: The primary visual cortex (V1) in individuals born blind is engaged in a wide spectrum of tasks and sensory modalities, including audition, touch, language, and memory. This widespread involvement raises questions regarding the constancy of its role and whether it might exhibit flexibility in its function over time, connecting to diverse network functions in response to task-specific demands. This would suggest that reorganized V1 takes on a role similar to cognitive multiple-demand system regions. Alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…FC patterns of typically developed individuals have been shown to be primarily shaped by common group and stable individual features, and not by time, state or task (Finn et al, 2015; Gratton et al, 2018; Tavor et al, 2016). Further, we have recently shown that individual FC patterns are stable across time and state even in the context of plasticity due to visual deprivation (Amaral et al, 2023). Therefore, there should not to be meaningful differences between resting-state and task FC networks.…”
Section: Discussionmentioning
confidence: 99%
“…FC patterns of typically developed individuals have been shown to be primarily shaped by common group and stable individual features, and not by time, state or task (Finn et al, 2015; Gratton et al, 2018; Tavor et al, 2016). Further, we have recently shown that individual FC patterns are stable across time and state even in the context of plasticity due to visual deprivation (Amaral et al, 2023). Therefore, there should not to be meaningful differences between resting-state and task FC networks.…”
Section: Discussionmentioning
confidence: 99%